A study of nonverbal expression in the Spongebob movie - Shariful Ruzi, Nurul Husna; Abdullah, Nur Nabilah (Kulliyyah of Languages and Management, IIUM, 2022)
Nonverbal expressions are one of the nonverbal communication elements that can convey messages. Nonverbal expression can include body movement, gestures, eye contact, tone of voice, and facial expression. Nonverbal communication has played a critical role in the development of cartoon and animated characters. The Spongebob Squarepants film 'Sponge on the Run' is one of the most popular animated films in the entertainment industry aimed at a younger audience. The purpose of this paper is to investigate how effective nonverbal expressions are used to represent the characters in the Spongebob movie 'Spongebob on the Run.' The study's audio-visual data was gathered from the online movie service 'Netflix,' and the applied conversation analysis method was employed. The findings from interaction analysis the showed that each character in the cartoon used different nonverbal expressions to support the meaning for verbal communications. Furthermore, the findings revealed the effectiveness of nonverbal expressions used in relation to culture and to support verbal messages